Professional practice manual for electrical engineers and electricians. - Professional Practice Committee. Institute of Integrated Electrical Engineers of the Philippines (Quezon City, Philippines: Institute of Integrated Electrical Engineers of the Philippines., 1996)
The practice of Electrical Engineering involves the arts and science of developing, applying and controlling the electrical, electronic and related phenomena and nature for the benefit of mankind notably in the field of light, heat, power, communication and transportation .
Chapter1. Introduction -- Chapter2. Scope of Professional Services -- Chapter3. Compensation
Keywords: ELECTRICAL ENGINEERING -- PRACTICE MANUAL; ELECTRIC MACHINERY